Tour boats and dolphins: A note on quantifying the activities of whalewatching boats in the Shannon estuary, Ireland - Berrow, Simon; Holmes, Brian (J. Cetacean Res. Manage., 1999)
Commercial whalewatching of bottlenose dolphins, Tursiops truncatus, in the Shannon estuary, Ireland first began in 1993. This note attempts to quantify the development of this industry and operational procedures of commercial tour boats. Up to four vessels are involved, which carry out annually about 200 trips in total, involving ca 2,500 passengers, mainly (78%) in July and August. Thirty-six trips were accompanied, mainly in July 1997 and 1998, to record the search pattern and location at which tour boats observed dolphins and to identify the individual dolphins watched. The time to locate dolphins, total number observed and group size on each trip varied between years and between ports. There is some evidence that dolphins were less abundant and further upriver in 1998 compared to 1997. Operators from each port tended to search for dolphins in different areas and, over the short summer sampling period, largely watched different groups of dolphins to each other. The implications for management and the development of a sustainable whalewatching industry in the Shannon estuary are discussed.